Perlindungan Lahan Pertanian Pangan Berkelanjutan dalam Mendukung Pelestarian Subak - Made Putra Suryawan (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
In the Government Regulation Number 23 Year 1982 concerning irrigation, in Article 1 (h) it is affirmed the meaning of "Subak", namely as a socio-agrarian customary law community, being religious that has historically grown and developed as an organization in the field of water use at the farm level. Subak cannot be separated from food plantation and agricultural land, "krama subak" and its relationship with the Creator of the universe (the God). Subak in Bali is based on the philosophy of "Tri Hita Karana" which can be seen as a system because subak contains three main components, namely "parhyangan (God), pawongan (man), and palemahan (nature), which are closely related to each other. "Tri Hita Karana" consists of components of human relations with God / creator, human relations with humans, and human relations with their natural environment. In subak irrigation cannot be separated from food cropland, so that sustainable agricultural land will have an impact on subak's sustainability in Bali.